2012
DOI: 10.2174/1874440001206010026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Event-Related Desynchronization and Synchronization during the Auditory Oddball Task in Schizophrenia Patients

Abstract: Objective:We studied differences in the spatiotemporal dynamics of cortical oscillation across brain regions of patients with schizophrenia and normal subjects during the auditory oddball task using magnetoencephalography (MEG) and electroencephalography (EEG).Methods:Ten right-handed male schizophrenia patients were studied. We used a newly developed adaptive spatial filtering algorithm optimized for robust source time-frequency reconstruction of MEG and EEG data, and obtained consecutive images in functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The temporal lobe plays a central role in many symptoms associated with schizophrenia, including altered cognitive function, oversensitization to sensory stimuli, and auditory hallucinations (Boyer et al, 2007; Brady et al, 2010; Bruder et al, 1999; Fujimoto et al, 2012). Structural and functional abnormalities of STG and hippocampus have been reported in this illness, while quantitative investigations have demonstrated reductions in neuronal size, cortical glial cell number, as well as changes in neuronal density (Boyer et al, 2007; Bruder et al, 1999; Heckers, 2001; Rajarethinam et al, 2004; Rajarethinam et al, 2000; Steen et al, 2006); (Benes et al, 1991; Cotter et al, 2002; Heckers and Konradi, 2002; Uranova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal lobe plays a central role in many symptoms associated with schizophrenia, including altered cognitive function, oversensitization to sensory stimuli, and auditory hallucinations (Boyer et al, 2007; Brady et al, 2010; Bruder et al, 1999; Fujimoto et al, 2012). Structural and functional abnormalities of STG and hippocampus have been reported in this illness, while quantitative investigations have demonstrated reductions in neuronal size, cortical glial cell number, as well as changes in neuronal density (Boyer et al, 2007; Bruder et al, 1999; Heckers, 2001; Rajarethinam et al, 2004; Rajarethinam et al, 2000; Steen et al, 2006); (Benes et al, 1991; Cotter et al, 2002; Heckers and Konradi, 2002; Uranova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while abnormalities of oscillations in schizophrenia have been observed across a wide range of frequencies [Doege et al, ; Fujimoto et al, ; Grutzner et al, ; Stephane et al, ; Uhlhaas and Singer, ], evidence implicates beta‐band abnormalities specifically in perceptual integration: Uhlhaas et al [] observed that deficits in Gestalt perception in schizophrenia were specifically associated with reduced beta‐band phase synchrony between spatially remote sites, while Sun et al [] using a similar perceptual task, showed reduced correlation between beta‐band oscillations and high gamma band activity in first episode cases of schizophrenia relative to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown structural and functional abnormalities in temporal lobe brain regions in schizophrenia [13,58,64,65]. Schizophrenia patients showed smaller anterior, but not posterior, hippocampal volumes, and larger P50 and M50 gating ratios than controls [66].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in oscillations in high gamma bands in this study may be related to cross-frequency coupling between gamma and theta oscillation. We reported that the ERS power in the theta band (4–8 Hz) during the oddball task in the schizophrenia patient group was significantly increased in the left temporal pole at 250–500 ms, and was significantly increased in the dorsal and medial frontal and anterior portions of the anterior cingulate cortex in both hemispheres, and the left lateral temporal regions at 500–750 ms, compared to the control group [13]. Dysfunction in the gamma band in schizophrenia, probably due to cross-frequency coupling, may reflect disturbances in the encoding of new information related to the hippocampal theta rhythm induced in the cortex via hippocampo-cortical feedback loops or vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation